Peluang Riset Strategi Bumdes Sebagai Dasar Pengembangan Perekonomian Masyarakat: Sebuah Studi Literatur - M Ihsan; Irma Irma; Burhanuddin Ladjin; Arif Widyatama (Vokasi : Jurnal Riset Akuntansi, 2020)
The purpose of this article is to discover the potential for research on BUMDes strategies. This article is considered important because research on BUMDes is still very limited so that it can make a very large contribution to BUMDes research space. Bumdes has an important role in building the economy in the village. However, the condition that occurs is that there are still many conditions of rural community human resources, especially Bumdes officials, who do not have good management skills and financial literacy in managing Bumdes. This research was conducted with a literature study using Leximancer to determine the potential for future research. The results of this study indicate that there are 4 (four)  important variables that need to be considered by further research, namely environmental, business, innovation and performance.